(untitled) - Angel, James J. (Pennsylvania US, 1999)
Equity Flex Options is a practical guide showing how E-FLEX options can reduce the market impact of the sale or purchase of a large block of stock, repurchase stock for the account of its corporate issuer, and help manage potential risk.
Keywords: Portfolio management,Wrap accounts,Asset allocation,Phân bổ tài sản,Danh mục đầu tư